Carl Rogers’ notion of “self-actualization” in Joyce’s A Portrait of the Artist as a Young Man - Yazdani, Saeed; Ross, Stephen (Penerbit Universiti Kebangsaan Malaysia, 2019)
Loss of identity, alienation, and self-actualization, along with the split in self, are important ideas of literary works belonging to the first half of the twentieth century. Carl Rogers has pointed out to the split between the real and ideal self. He describes self-actualization as a fluid process and the self as an essential part of one’s personality that determines how one relates to the world. Rogers believes that the real self is a self-concept that a person might experience, whereas the ideal self is the one that person would like to achieve. This article analyzes the personality of the protagonist of James Joyce's A Portrait of the Artist as a Young Man, Stephen Dedalus, using Carl Rogers' notion of self and self-actualization, with particular reference to the incongruency of the real and ideal self. Roger's notion of the self, has not yet been applied on Joyce's works in the previous studies, and so is highlighted here in relation to A Portrait of the Artist as a Young Man.